Hydatidosis of the hip - Sanjurjo, Liber Mauro; Pavón Davila, Raúl (Cirugía del Uruguay, 1973)
Hydatid disease is particularly serious in thigh loction. Latency stage extends over a prolonged period and diagnosis is not made at a sufficiently early stage. Disease is progressive and invading, with destruction of bone tissue. Bone has no defense, is destroyed and passive. to parasite injury. Diagnosis is based on biolo;ical reactions. When X-rayed, lesions appear as areas of bone destruction, fil!ing defects or geodic images or "motheaten bone". This geodic osteosis process varies in extent and has no precise limits; there is no limiting reactional osteogenesis. Shape of bone is generally preserved. In exceptional cases bone may have a "deep fissure". There is bipolar geodic osteosis not affecting the joint and hydatid osteoarthritis in advanced forms. Eleven cases were studied: 8 men and 3 women. Lesions were locally malign and demanded early and radical treatment. This comprises two basic aspects: biological and surgical. Use of 33 o sodium chloride saturated solution, as proposed by Velarde Pérez, has become general and complements surgery. If located in cervical epiphysis of femur, Girlsdestone's operation makes total resection of lesion possible. Pelvian sector topography, involving cotyloid cavity (acetabulum). requires hemipelvectomy with partial resection of ilio-ischio-pubic sector; Limb may be preserved or not. This technique has been described by Dr. Guglielmone.